Media Pembelajaran Interaktif Nearpod dalam Meningkatkan Partisipasi Belajar Siswa pada Mata Pelajaran Al-Qur’an Hadis di Madrasah - Endah Sucia Dewi; Jasiah (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to describe the use of Nearpod as an interactive learning medium in enhancing students’ learning participation in the Al-Qur’an Hadith subject at a Madrasah Tsanawiyah. The research employed a qualitative approach with a descriptive qualitative design. The research subjects consisted of Al-Qur’an Hadith teachers and seventh-grade students of MTsN 2 Katingan. Data were collected through observation, interviews, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing, supported by triangulation to ensure data validity. The findings indicate that the use of Nearpod significantly improves the quality of the Al-Qur’an Hadith learning process. Learning activities become more engaging and student-centered, resulting in higher levels of focus, enthusiasm, and active participation among students. Interactive features such as quizzes, polls, videos, and manipulative exercises encourage student involvement in responding to questions, participating in discussions, and completing learning tasks. Furthermore, Nearpod increases students’ learning motivation and assists teachers in delivering instructional materials in a more varied and well-structured manner. Therefore, Nearpod is effective as a digital learning medium in Madrasah contexts